2017
DOI: 10.5812/jjm.12798
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Sarcocystis spp. in Sheep and Cattle by PCR-RFLP from Southwest of Iran

Abstract: Background: Sarcocystis species are obligatory intracellular parasites of many vertebrate hosts. Some pathogen species cause major economic loss and hygienic problems in the animal and human population, respectively. Objectives: The goal of the current study was conducted to identify Sarcocystis species in meat-producer animals and to evaluate the risk of transmission of parasites after consumption of infected meat by humans. Methods: Fifty samples of sheep and cattle muscles were collected from the abattoir. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…Based on the data reported by Nourani et al [34], the thin-walled sarcocysts in cattle were consistent with S. cruzi with higher prevalence, and the thickwalled sarcocysts could represent S. hominis with lower prevalence. Both S. cruzi and S. tenella were found at higher prevalence rates of 100% and 80% by Daryani et al [20] and Rahdar and Kardooni [42], respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Based on the data reported by Nourani et al [34], the thin-walled sarcocysts in cattle were consistent with S. cruzi with higher prevalence, and the thickwalled sarcocysts could represent S. hominis with lower prevalence. Both S. cruzi and S. tenella were found at higher prevalence rates of 100% and 80% by Daryani et al [20] and Rahdar and Kardooni [42], respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Although, molecular methods are insufficiently convenient for species identifications because of high genetic similarity; the ultrastructure observation of primary cyst wall technique is considered to be one possible reliable method for identifying Sarcocystis spp (6,7). Based on the reports from different provinces of Iran, infection rate of sarcocystosis in adult bovine muscles is absolutely high (8)(9)(10)(11)(12)(13)(14)(15), but there is no information about intensity of this parasitic disease in Sistan region. So, the present research aims to determine the intensity of infection and histopathological investigation of Sarcocystis spp.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, 97% of the heart samples were found to be positive for Sarcocystis and were identified as S. cruzi (100%). These findings should be considered by the veterinary organization, because S. cruzi, despite having no pathologic effects on humans, has severe effects on the livestock and can lead to severe clinical sign, abortion, weight loss, neurologic sign, fever, loss of animal products and death ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%